THE INFLUENCE OF SELF-ACCEPTANCE AND SELF-FULFILLMENT ON BEAUTY ANXIETY IN BEAUTY VLOGGER AUDIENCES - An-Nisa, Lhulu -; Putri, Inayah Sherly Restika; Bimantoro, Demanda -; Razen, Elvina Roseva; Rosalina, Rosta -; Mukhlida, Hilma Miladiya Fauza; Eva, Nur -; Dharmastuti, Anjarie - (Universitas Muhammadiyah Surakarta, 2024)
During adolescence, individuals will experience a transition from childhood and adulthood. There will be many changes in behavior in response to difficult situations and environments, one of which is regarding personal appearance. The research aims to determine the influence of Self-Acceptance and Self-Fulfillment on Beauty Anxiety in Beauty Vlogger audiences. The research method used is quantitative. After distributing the questionnaire link to the population, there were 50 participants who met the criteria for filling out the Self-Acceptance (X1), Self-Fulfillment (X2), Beauty Anxiety (Y) questionnaires. The results of the variable normality test have sequential values of 0.063; 0.082; 0.056 which means more than the sig value. 0.05 so that all variables are normally distributed. Then, the linearity results show that the two variables, both self-acceptance and self-fulfillment, have a linear relationship with beauty anxiety. The results of the analysis using SPSS show that there is an influence of Self-Acceptance and Self-Fulfillment on Beauty Anxiety. A person needs to have a high score on Self-Acceptance and Self-Fulfillment to be able to minimize anxiety about appearance (beauty anxiety).